Answer:
k = 6 or k = -6
Explanation:
The standard form of the quadratic equation is
....[1]
The roots of this equation can be determined using the quadratic formula:
![x = ( -b \pm √(b^2 - 4ac))/( 2a )](https://img.qammunity.org/2023/formulas/mathematics/high-school/8tzy3vplb3s5alylo5jtbobmewwfnwo7nq.png)
When
there is one real root
When
there are two real roots
When
there are two imaginary roots
First let's convert the equation
![x + k + (9)/(x) = 0](https://img.qammunity.org/2023/formulas/mathematics/high-school/kxb4dh2y3tudxw4dh8vycaz079o4w5g2sq.png)
into its standard form by multiplying both sides by x
We get
[2]
By comparing this standardized form to the general standard form we can see that the coefficient of x², namely a is 1, the coefficient of x, namely b is k and c is 9
So we have
a = 1
b = k
c= 9
Since we are given that there is only one root and therefore b²-4ac = 0 lets plug in these values of a, b and c
We get k² - 4·1·9 = 0
==> k² - 36 = 0
==> k² = 36
==> k = ±√36
===> k = ±6
So the two possible values of k are k = 6 and k = -6
So the equations become
x² + 6x + 9 = 0 whose roots are x = -3 and x = -3
and
x² -6x + 9 = 0 whose roots are x = 3, x = 3
In both cases the roots are the same
Hope that helps